(untitled) (Medico Legal Update, 2019)
Considering Article 28 H of the fourth amendment to the Republic of Indonesia’s 1945 Constitution, there is citizen’s constitutional right, the right to health and to get healthcare service. Therefore, all healthcare services should fulfill right and obligation of service provider and patient, and medical service standard. Esthetic beauty clinic as a private health service should fulfill it compulsorily. This article studied the factors making the law protection for the patients of esthetic beauty clinic in Indonesia not fulfilling yet the citizen’s constitutional right. This study was conducted on stakeholders of esthetic beauty clinic in five provinces in ten cities of Indonesia, using empirical qualitative method. The result of research showed that the factors the law protection for the patients of esthetic beauty clinic in Indonesia not fulfilling yet the citizen’s constitutional right.